استخدام بعض الأنواع الجرثومية لإنتاج الميتانول والايتانول من مياه الجفت - قره علي, أحمد; العلي, بدر; زوان, ميس (Latakia University Journal -Biological Sciences Series, 2016)
يتناول هذا البحث إمكانية إنتاج كل من الميتانول والايتانول من مياه الجفت OMW((OMW: Olive Mill Wastewater، وذلك خلال عملية معالجة حيوية لاهوائية (تخمر) باستخدام جراثيم ممرضة وأخرى معزولة بحرياً. أظهرت النتائج أنه عند تخمر مياه الجفت باستخدام جراثيم الـSalmonella sp. كان أعلى تركيز للميتانول (g/lµ5658.308) عند تركيز مياه الجفت 7.5% في وسط التخمر، وأعلى تركيز للايتانول(g/lµ49.132) عند تركيز17.5% لمياه الجفت.في حين أعطت جراثيم الـPseudomonas sp. أعلى تركيز للميتانول g/l)µ603.76) والايتانول (g/lµ688.71) عند تركيز 17.5%لمياه الجفت.بينت النتائج قدرة الجراثيم المعزولة من مياه البحر على إنتاج الميتانول و الايتانول؛ بالنسبة لجراثيمX3 تبين وجود علاقة طردية بين ارتفاع تراكيز مياه الجفت (15 , 35,50 )% وارتفاع تراكيز الميتانول (UL, g/lµ130.406, g/lµ1353.244) على التوالي، على عكس الايتانول الذي كان تحت حدود الكشف (Under limited: UL).In this study, we review the possibility of production both ethanol and methanol from OMW(OMW: Olive Mill Wastewater), fermented using pathogenic bacteria and isolated marine bacteria. The results showed that when using Salmonella sp. bacteria, the highest values of methanol (5658.308 μg /l) appear at 7.5% concentration of the OMW, and the higher concentration of ethanol (49.132 μg/l) at a concentration of 17.5% fermentation of OMW. While Pseudomonas sp. produced the highest concentration of methanol (603.76μ g/l) and ethanol (688.71μg /l) at 17.5% for OMW. The results of this research showedthe ability of the bacteria isolated from sea water in producing the above mentioned alcohols; for example the X3 bacteria displayed a direct correlation between high concentrations of OMW (15 , 35 , 50)% and the high concentrations of produced methanol (UL, 130.406μg/l, 1353.244μg/l ), apposite to ethanol which was under the detection limits (under limited: UL).